Invisible : theology and the experience of Asian American women - Kim, Grace Ji-Sun, 1969- (Fortress Press, 2021)
"Grace Ji-Sun Kim examines encounters with racism, sexism, and xenophobia as she works toward ending Asian American women's invisibility. She deploys biblical, sociological, and theological narratives to empower the voices of Asian American women. And she shares the story of her heritage, her family history, her immigration, and her own experience as an Asian American woman. Speaking with the weight of her narrative, she proclaims the histories, experiences, and voices of Asian American women must be rescued from obscurity. Speaking with the weight of a theologian, she powerfully paves the way for a theology of visibility that honors the voice and identity of these women. As Asian American women work toward a theology of visibility, they uplift the voiceless and empower the invisible, moving beyond experiences of oppression and toward claiming their space in the kin-dom of God."--Back cover.